Analyzing subcomponents of affective dysregulation in borderline personality disorder in comparison to other clinical groups using multiple e-diary datasets. Issue 1 (December 2016) - Santangelo, P.; Limberger, M.; Stiglmayr, C.; Houben, M.; Coosemans, J.; Verleysen, G.; Kuppens, P.; Tuerlinckx, F.; Vanpaemel, W.; Ebner-Priemer, U.
Abstract Background Affective dysregulation is widely regarded as being the core problem in patients with borderline personality disorder (BPD). Moreover, BPD is the disorder mainly associated with affective dysregulation. However, the empirical confirmation of the specificity of affective dysregulation for BPD is still pending. We used a validated approach from basic affective science that allows for simultaneously analyzing three interdependent components of affective dysregulation that are disturbed in patients with BPD: homebase, variability, and attractor strength (return to baseline). Methods We applied two types of multilevel models on two e-diary datasets to investigate group differences regarding three subcomponents between BPD patients (n =  43;n =  51) and patients with posttraumatic stress disorder (PTSD;n =  28) and those with bulimia nervosa (BN;n =  20) as clinical control groups in dataset 1, and patients with panic disorder (PD;n =  26) and those with major depression (MD;n =  25) as clinical control groups in dataset 2. In addition, healthy controls (n =  28;n =  40) were included in the analyses. In both studies, e-diaries were used to repeatedly collect data about affective experiences during participants' daily lives. In study 1 a high-frequency sampling strategy with assessments in 15 min-intervals over 24 h was applied, whereas the assessments occurred every waking hour over 48 h in study 2. The local ethics committees approved both studies, and all participants provided written informed consent. Results In contradiction to our hypotheses, BPD patients did not consistently show altered affective dysregulation compared to the clinical patient groups. The only differences in affective dynamics in BPD patients emerged with regard to one of three subcomponents, affective homebase. However, these results were not even consistent. Conversely, comparing the patients to healthy controls revealed a pattern of more negative affective homebases, higher levels of affective variability, and (partially) reduced returns to baseline in the patient groups. Conclusions Our results indicate that affective dysregulation constitutes a transdiagnostic mechanism that manifests in similar ways in several different mental disorders. We point out promising prospects that might help to elucidate the common and distinctive mechanisms that underlie several different disorders and that should be addressed in future studies.